STANDARDISASI KUALITAS EKSTRAK BATANG BROTOWALI (Tinospora crispa) - Harwoko Harwoko; Nur Amalia Choironi (Majalah Obat Tradisional, 2016)
Brotowali (Tinospora crispa) has been traditionally used for the treatment of gout and scientifically reported as analgesic, anti-inflammatory, and antihyperuricemic agents. Tinospora crispa stem is one of herbal medicine material that its quality should be standardized. This study aims to determine the quality parameters of the T. crispa ethanolic extract included specific and non-specific parameters. Brotowali stem were macerated using ethanol 70%, then the non-specific parameters such as the water content, total ash, total contaminant number of bacteria and fungus were determined. The specific parameters including organoleptic properties, water soluble extract, ethanol soluble extract, and the thin layer chromatography (TLC) profile have also been determined. The parameter values were compared to the qualification of traditional medicine from Department of Health (Depkes R.I.). The result showed that T.crispa stem ethanolic extract has the water content was 8.12±0.06% and the total ash was 5.20 ± 0.12%. The microbiology results showed that the total contaminant of bacteria as much as 5 x 102 CFU/g and fungus as much as 5 x 103 CFU/g. This extract was brown viscous extract, bitter taste and characteristic odor with water soluble fraction was 45.09 ± 0.67% and ethanol soluble fraction was 14.19 ± 0.14%. The TLC profile of ethanolic extract indicates the existence of flavonoids and alkaloids. Total flavonoids of brotowali extract (32.65 ± 0.20%) rutin equivalent.